2008
DOI: 10.1007/s10823-008-9074-6
|View full text |Cite
|
Sign up to set email alerts
|

Informal and Formal Long-term Care for Frail Older Adults in Cairo, Egypt: Family Caregiving Decisions in a Context of Social Change

Abstract: This paper explores the factors that lead family caregivers to place their frail older relatives into long-term care centers in Cairo, Egypt despite norms of family care. Semi-structured interviews were conducted with 18 "case" caregivers who placed their older relatives into long-term care and 17 "control" caregivers who provided for their older relatives at home. Cases and controls differed in their relationship to the older adult, number and proximity of supportive siblings, and perceived health status of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 16 publications
1
56
0
Order By: Relevance
“…Some of these institutions continue to treat communicable diseases such as leprosy. The long-term institutions in the region are usually operated by voluntary, not-for-profit, charitable religious associations with financial support from the ministry of health as well as donations from the community [19]. The government support is based on a flat daily rate per patient.…”
Section: Long-term Care and Palliative Carementioning
confidence: 99%
“…Some of these institutions continue to treat communicable diseases such as leprosy. The long-term institutions in the region are usually operated by voluntary, not-for-profit, charitable religious associations with financial support from the ministry of health as well as donations from the community [19]. The government support is based on a flat daily rate per patient.…”
Section: Long-term Care and Palliative Carementioning
confidence: 99%
“…Also, eliciting reliable information about family care-giving practices is highly problematic, since responses (especially to quantitative surveys) are strongly influenced by cultural norms of acceptable behaviour (Yanxia Zhang and Yeung, 2012;Sinunu et al, 2009). Put simply, household members will not necessarily admit to themselves, let alone to an outsider, that the care they provide is inadequate.…”
Section: The Role Of Academic Research In Problem Definitionmentioning
confidence: 99%
“…There is an extensive and mixed literature on tradeoffs between caring for seniors and female labor force participation, some finding evidence of a tradeoff, and others finding that caring for an aging parent does not reduce the amount of time women spend in the labor force, since co-residing parents can provide care for young children, freeing up time for formal work (Johnson and Lo Sasso 2006;Latif 2006;Maurer-Fazio et al 2011;Sasaki 2002;Wakabayashi and Donato 2005;Wolf and Soldo 1994). Qualitative research in Egypt has suggested that with rising levels of female employment, there is increasing tension between women's labor force participation and their ability to care for aging in-laws (Sinunu, Yount, and El Afify 2008). Especially among wealthier, urban, and more-educated households, there is evidence that families are beginning to seek formal care or non-family member care options for aging parents (removing the burden from daughters-in-law).…”
Section: Women's Labor and Leisurementioning
confidence: 99%